High and low worriers do not differ in unstimulated resting-state brain connectivity - Fanny Weber-Goericke; Markus Muehlhan (Scientific Reports, 2023)
Abstract Chronic, excessive and uncontrollable worry presents an anxiety rising and distressing mental activity relevant in a range of psychological disorders. Task based studies investigating its underlying neural mechanisms reveal fairly heterogenous results. The current study aimed to investigate pathological worry related effects on the functional neural network architecture in the resting unstimulated brain. Using resting-state functional magnetic resonance imaging (rsfMRI) we compared functional connectivity (FC) patterns between 21 high worriers and 21 low worriers. We, on the one hand, conducted a seed-to-voxel analysis based on recent meta-analytic findings and, on the other hand, implemented a data-driven multi voxel pattern analysis (MVPA) approach to yield brain clusters showing connectivity differences between the two groups. Additionally, the seed regions and MVPA were used to investigate whether whole brain connectivity is associated with momentary state worry across groups. The data did not reveal differences in resting-state FC related to pathological worry, neither by the seed-to-voxel or MVPA approach testing for differences linked to trait worry nor by using the MVPA to test for state worry related aberrations. We discuss whether the null findings in our analyses are related to spontaneous fluctuations in momentary worry and the associated presence of multiple fluctuating brain states that could cause mutually cancelling effects. For future studies investigating the neural correlates of excessive worry, we propose a direct worry induction for better control of the situation.